CONTROL SYSTEM SIMULATION DESIGN NODEMCU ESP 8266 MICROCONTROLLER BASED HOME LIGHTING - Hariyadi, Slamet; Kustori, Kustori; Hartono, Hartono; Faizah, Fiqqih (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This learning tool is made with the aim that readers can learn or get to know about microcontrollers and one of their uses and applications. In addition, the author tried something new, namely simulating a home lighting control system based on the NodeMCU ESP 8266 microcontroller which works automatically by utilizing RTC (Real Time Clock) so that it can work according to the time and conditions that have been determined so that when left at home as in an inhabited state. The working principle of this design is programming on a microcontroller that has been set with certain time settings, which will be processed and the result is in the form of real time and the state of the lights will be displayed in the LCD and mock up. By simulating a home lighting control system based on the nodemcu esp 8266 microcontroller, the author has several conclusions, namely this tool can be operated to turn on porch lights and living room lights remotely without having to be in place using the android application, namely Blynk, The ability of this tool can detect objects using PIR sensors so as to make the living room lights turn on automatically to minimize the occurrence theft, The porch light can turn on automatically every 5:00 p.m. and turn itself off at 6:00 a.m.